User-Agent Bond in Generalizable Environments: Long-Term Risk-Reduction via Nudged Virtual Choices - Wang, Liyuan; Christensen, John L.; Smith, Benjamin J.; Gillig, Traci K.; Jeong, David C.; Liu, Mingxuan; Appleby, Paul R.; Read, Stephen J.; Miller, Lynn C. (Frontiers in Psychology, 2021)
Avatars or agents are digitized self-representations of a player in mediated environments. While using agents to navigate through mediated environments, players form bonds with their self-agents or characters, a process referred to as identification. Identification can involve automatic, but temporary, self-concept “shifts in implicit self-perceptions” (Klimmt et al., 2010, p. 323) of the media user by adopting or emphasizing the action choices on behalf of the social expectation of the avatar in the mediated environment. In the current study, we test the possibility that users' identification with video game avatars–a bond built between avatars and players- would account for subsequent behavior changes. We did so by using 3-month longitudinal data involving a narratively-based serious game: Socially Optimized Learning in Virtual Environments (SOLVE), a 3D-interactive game designed to reduce risky sexual behaviors among young men who have sex with men (n = 444). Results show that video game identification predicts both the reduction of risky sexual behaviors over time, and reduction in the number of non-primary partners with whom risky sex occurs. And when players identify with the game character, they tend to make healthier choices, which significantly mediates the link between video game identification and reduction of risky behaviors.